Предмет: Математика,
автор: Arsenikp
-6(3х+1)-(х-8)=15; -3(2х+1)-(х-8)=7; -7(3х+6)-(х-8)=-15; -7(2х+3)-(х-5)=-9
Ответы
Автор ответа:
0
-18х-6-х+8=15
-19х+2=15
-19х=13
х=-1 6/3
-6х-3-х+8=7
-7х+5=7
-7х=2
х= -3 1/2
-21х-42-х+8=-15
-22х-34=-15
-22х=9
х= - 2 4/9
-14х-21-х+5=-9
-15х-16=-9
-15х=7
х= -2 1/7
-19х+2=15
-19х=13
х=-1 6/3
-6х-3-х+8=7
-7х+5=7
-7х=2
х= -3 1/2
-21х-42-х+8=-15
-22х-34=-15
-22х=9
х= - 2 4/9
-14х-21-х+5=-9
-15х-16=-9
-15х=7
х= -2 1/7
Автор ответа:
0
Огромное спасибо!
Похожие вопросы
Предмет: История,
автор: samsuns12345grant
Предмет: Қазақ тiлi,
автор: neizvestno1116
Предмет: Алгебра,
автор: Bruno78
Предмет: Информатика,
автор: Bandamario
Предмет: Алгебра,
автор: Deld